cAMP Receptor Protein Positively Regulates the Expression of Genes Involved in the Biosynthesis of Klebsiella oxytoca Tilivalline Cytotoxin - Rodríguez-Valverde, Diana; León-Montes, Nancy; Soria-Bustos, Jorge; Martínez-Cruz, Jessica; González-Ugalde, Ricardo; Rivera-Gutiérrez, Sandra; González-y-Merchand, Jorge A.; Rosales-Reyes, Roberto; García-Morales, Lázaro; Hirakawa, Hidetada; Fox, James G.; Girón, Jorge A.; et al. (Frontiers in Microbiology, 2021)
Klebsiella oxytoca is a resident of the human gut. However, certain K. oxytoca toxigenic strains exist that secrete the nonribosomal peptide tilivalline (TV) cytotoxin. TV is a pyrrolobenzodiazepine that causes antibiotic-associated hemorrhagic colitis (AAHC). The biosynthesis of TV is driven by enzymes encoded by the aroX and NRPS operons. In this study, we determined the effect of environmental signals such as carbon sources, osmolarity, and divalent cations on the transcription of both TV biosynthetic operons. Gene expression was enhanced when bacteria were cultivated in tryptone lactose broth. Glucose, high osmolarity, and depletion of calcium and magnesium diminished gene expression, whereas glycerol increased transcription of both TV biosynthetic operons. The cAMP receptor protein (CRP) is a major transcriptional regulator in bacteria that plays a key role in metabolic regulation. To investigate the role of CRP on the cytotoxicity of K. oxytoca, we compared levels of expression of TV biosynthetic operons and synthesis of TV in wild-type strain MIT 09-7231 and a Δcrp isogenic mutant. In summary, we found that CRP directly activates the transcription of the aroX and NRPS operons and that the absence of CRP reduced cytotoxicity of K. oxytoca on HeLa cells, due to a significant reduction in TV production. This study highlights the importance of the CRP protein in the regulation of virulence genes in enteric bacteria and broadens our knowledge on the regulatory mechanisms of the TV cytotoxin.